Important Strategies in Mitigating Cyber Threats Using SLR in the Student Environment: Strategi Penting dalam Mengurangi Ancaman Siber Menggunakan Tinjauan Literatur (SLR) di Lingkungan Mahasiswa - Herdianto Sukmana; Fathoni; Dani (FKOM UNIKU, 2026)
In the ever-evolving digital era, cyber threats are increasingly diverse and demand effective mitigation strategies, especially for the educational environment and students who are easy targets for human error-based attacks. This study aims to analyze the role of cybersecurity awareness as an important strategy in mitigating cyber threats using the Systematic Literature Review (SLR) approach. A review was conducted on the literature that implements four main cybersecurity frameworks, namely NIST CSF, COBIT 5, the KAMI Index, and ISO/IEC 27001. The results of the analysis show that the technological aspect alone is not enough to guarantee security; Individual and organizational awareness—especially in the education sector, SMEs, and remote work environments—has a significant contribution to lowering the risk of cyber incidents. This study emphasizes that systematic, measurable, and framework-based awareness increase can strengthen cyber defense and support the development of a security culture among students.